Optimization of 5-kW Mobile and Portable PEMFC System via Energy Integration - Siti Kartom Kamarudin; Wan Ramli Wan Daud; Ayub Md. Som; Jr. Abdul Wahab Mohammad; Mohd. Sobri Takrif (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
he main objective of this study is to design an energy recovery system for the Proton Electrolyte Membrane Fuel Cell (PEMFC) that will optimize energy use through heat integration. A PEMFC system with a power output of 5 kW was used in the case study. Methanol, which served as primary fuel source of the autothermal reformer (ATR) system, was fed together with steam and oxygen. Based on the conceptual design, the ATR product contains about 73% H2' 2% CO, and 25% C02' The hydrogen-rich reform ate produced by reforming primary fuels in the fuel proC€t::30r ystem, which scontains a significant amount of CO, was reduced further via Water Gas Shift (WGS) reactor, Tubular Ceramic Membrane (TCM), and Pressure Swing Adsorber (PSA) in series. From the plots, the pinch point was determined at 540°C,the minimum process heating requirement from hot utilities QH mon at 140 W, and the minimum process cooling requirement from cold utilities Qc. at 96 W. Furthermore, energy recovery for both heating and cooling purposes aft ; heat integration registered at 92% and 95%, respectively. Also, the number of heat exchangers reduced from 7 to 4 after heat integration.